1957
DOI: 10.1113/jphysiol.1957.sp005901
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium and potassium injected into the cerebral ventricles of the cat

Abstract: In previous experiments (Feldberg & Sherwood, 1954a, b, 1955 injections of a number of drugs into the lateral cerebral ventricles of the unanaesthetized cat and the ensuing behavioural changes have been described. The present experiments are a continuation of this work and deal with the effects of intraventricular injections of calcium and potassium. These cations are known to exert powerful central depressant and excitatory effects respectively when given systemically or applied locally, but only a few experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1958
1958
2006
2006

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Several decades ago Feldberg and Sherwood (1957) and Zuckermann and Glaser (1968) have shown that direct application of high K + solution to the brain of experimental animals can cause epileptiform convulsions. Later Korn et al (1987) reported that raising K + concentration in the organ bath induced seizure discharges in hippocampal tissue slices.…”
Section: Discussionmentioning
confidence: 99%
“…Several decades ago Feldberg and Sherwood (1957) and Zuckermann and Glaser (1968) have shown that direct application of high K + solution to the brain of experimental animals can cause epileptiform convulsions. Later Korn et al (1987) reported that raising K + concentration in the organ bath induced seizure discharges in hippocampal tissue slices.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known for some time that exposing the brain to a high concentration of K + can induce epileptiform discharge (Feldberg and Sherwood 1957;Zuckermann and Glaser 1968;Korn and others 1987;Chamberlin and Dingledine 1989) and that excess K + is released from neurons during seizures. The exudation of excess K + and uptake of Na + during seizure discharges could be detected with ion-selective glass electrodes placed on the cortical surface (Meyer and others 1961) and the fluxes of Fig.…”
Section: Potassium and Seizuresmentioning
confidence: 99%
“…Antipyretics are analgaesics, and the catecholamines, too, exert analgaesic effects when acting from the liquor spaces (Bass, 1914;Leimdorfer & Metzner, 1949;Feldberg & Sherwood, 1954, 1957 when applied directly to the hypothalamus (Myers, 1964) or when given subcutaneously (Radouco-Thomas, Nosal, Radouco-Thomas & Le Breton, 1959).…”
Section: New Concept Of Temperature Regulation 235mentioning
confidence: 99%